Postpartum Depression Among Malaysian Mothers During the COVID-19 Pandemic and Its Relationship With Breastfeeding Practices and Perceived Social Support - Thiagarajah, Kokila; Subramaniam, Suganya Bala; Michelle, Yeen Tan Ng (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Breastfeeding practice aids babies in acquiring nutrients they need but it could be impeded when women are struggling from postpartum depression (PPD). The prevalence of PPD varied across countries and certain sociodemographic traits along with breastfeeding practices have influenced PPD rates differently. The aim of this research was to study the prevalence of PPD among Malaysian mothers during the COVID-19 pandemic and to study the overall relationship between breastfeeding ractice with PPD and perceived social support. Methods: Through an online questionnaire, 109 mothers have participated, and the collected data were analysed based on the sociodemographic information, Edinburgh Postnatal Depression Scale (EPDS) and Multidimensional Scale of Perceived Social Support (MSPSS). Results: The prevalence of PPD was 48.6%. Sociodemographic characteristics like working status, ethnicity, living region and household income had no association with PPD. No statistically significant differences in working status with PPD and perceived social support levels respectively, although the occurrence of PPD was higher among working-class mothers. A significant negative correlation was found between PPD level with perceived social support (P=0.040, rs=-0.197) and paid maternity leave (P=0.015, rs=-0.333). Perceived social support was positively correlated with education level (P=0.044, rs=0.194) and paid maternity leave (P=0.023, rs=0.218). Conclusion: The social support and paid maternity leave may reduce the PPD, yet further studies involving a larger and more diverse subjects may warrant a more conclusive finding.